2020
DOI: 10.3390/molecules25020374
|View full text |Cite
|
Sign up to set email alerts
|

Honey Volatiles as a Fingerprint for Botanical Origin—A Review on their Occurrence on Monofloral Honeys

Abstract: Honeys have specific organoleptic characteristics, with nutritional and health benefits, being highly appreciated by consumers, not only in food but also in the pharmaceutical and cosmetic industries. Honey composition varies between regions according to the surrounding flora, enabling its characterization by source or type. Monofloral honeys may reach higher market values than multifloral ones. Honey’s aroma is very specific, resulting from the combination of volatile compounds present in low concentrations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 121 publications
(238 reference statements)
2
73
0
2
Order By: Relevance
“…O feniletanal foi identificado em todos os méis e é citado em diversos estudos como constituinte volátil de méis, cítricos e de eucalipto, empregado na formulação do aroma artificial de mel. O cis-óxido de linalol, identificado em todas as amostras, é também constituinte volátil desses e de outros diversos méis (Manyi-lohet al, 2011;Machado et al,2020).…”
Section: Propriedades Biológicasunclassified
“…O feniletanal foi identificado em todos os méis e é citado em diversos estudos como constituinte volátil de méis, cítricos e de eucalipto, empregado na formulação do aroma artificial de mel. O cis-óxido de linalol, identificado em todas as amostras, é também constituinte volátil desses e de outros diversos méis (Manyi-lohet al, 2011;Machado et al,2020).…”
Section: Propriedades Biológicasunclassified
“…Our predictive in silico analysis revealed that benzoic acid, a constituent of both Heather [ 58 ] and Manuka honey [ 59 ], could bind with a high efficiency into the pocket of Pa DsbA1 where the control ligand fits [ 20 ]. This binding occurs via H-bond interactions between the hydroxyl hydrogen of benzoic acid and the carbonyl oxygen of Pro20, and between the hydroxyl oxygen of benzoic acid and the phenolic hydrogen of Tyr148.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the traditional melissopalinological analysis is not effective in the authentication of filtered honeys and those whose pollen is underrepresented. For these reasons, for several years the scientific community has been developing instrumental analytical protocols aimed at relating specific markers or classes of compounds to the floral origin of honey, most of them summarized in a number of authoritative reviews [ 4 , 5 , 6 ]. In this context, chromatographic techniques have for years been a key tool in the search for specific markers.…”
Section: Introductionmentioning
confidence: 99%